Dry Amorphization of Itraconazole Using Mesoporous Silica and Twin-Screw Technology - Margarethe Richter; Simon Welzmiller; Fred Monsuur; Annika R. Völp; Joachim Quadflieg (MDPI AG, 2024)
Background/Objectives: Amorphization of an active pharmaceutical ingredient (API) can improve its dissolution and enhance bioavailability. Avoiding solvents for drug amorphization is beneficial due to environmental issues and potential solvent residues in the final product. Methods: Dry amorphization using a twin-screw extruder is presented in this paper. A blend of mesoporous silica particles and crystalline itraconazole was processed using a pharma-grade laboratory scale twin-screw extruder. The influence of different screw configurations and process parameters was tested. Particle size and shape are compared in scanning electron microscopy (SEM) images. Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) are used to determine the residual amount of crystalline itraconazole in the final product. Results: An optimized screw configuration for the process was found which leads to more than 90% amorphous API when processed at room temperature. Full amorphization was reached at 70 °C. The specific mechanic energy (SME) introduced into the material during twin-screw processing is crucial for the dry amorphization. The higher the SME, the lower the residual amount of crystalline API. Two months after processing, however, recrystallization was observed by XRD. Conclusions: Dry processing using a twin-screw extruder is continuous, free of solvents and can be performed at low temperatures. This study proves the concept of twin-screw processing with mesoporous silica for dry amorphization of itraconazole.